Visual "playback" of colorful signals in the field supports sensory drive for signal detectability. Issue 4 (9th June 2018) - Gunderson, Alex R; Fleishman, Leo J; Leal, Manuel; ,
Abstract: Colorful visual signals are important systems for investigating the effects of signaling environments and receiver physiology on signal evolution as predicted by the sensory drive hypothesis. Support for the sensory drive hypothesis on color signal evolution is mostly based on documenting correlations between the properties of signals and habitat conditions under which the signals are given (i.e., a correlational approach) and less commonly on the use of mathematical models that integrate representations of visual environments, signal properties, and sensory systems (i.e., a functional approach). Here, we used an experimental approach in the field to evaluate signal efficacy of colorful lizard throat fans called dewlaps that show geographic variation in the lizard Anolis cristatellus. We used a remote controlled apparatus to display "fake dewlaps" to wild lizards to test for adaptive divergence in dewlap brightness (i.e., perceived intensity) among populations in situ . We found evidence of local adaptation in dewlap brightness consistent with the sensory drive hypothesis. Specifically, dewlaps that had the brightness characteristics of local lizards were more likely to be detected than those with the brightness characteristics of non-local lizards. Our findings indicate that simplified mathematical representations of visual environments may allow robust estimates of relative detectability or conspicuousness in natural habitats. We have shown the feasibility of evaluating color signal efficacy experimentally under natural conditions and demonstrate the potential advantages of presenting isolated components of signals to an intended receiver to measure their contribution to signal function.